Operational analysis of bus lanes on arterials application and refinement. - St. Jacques, Kevin R.; Levinson, Herbert S. (Research results digest (Transit Cooperative Research Program), 2000)
"This TCRP digest provides the results of TCRP Project A-7A, "Field evaluation of bus lanes on arterials," conducted by Kevin R. St. Jacques, of Wilbur Smith Associates, in association with Herbert S. Levinson, Transportation Consultant."